Assessment of the psychometric properties of the resilience scale among university students in Saudi Arabia - Wan Shahrazad Wan Sulaiman,; Abdullah Ali AlShehry,; Rozainee Khairudin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Resilience is a widely studied variable in enhancing the protective factors and personal resources of individuals. The Resilience Scale is commonly used to measure resilience, but not many studies have reported the psychometric properties of the Arabic translated Resilience Scale. Therefore, this study aimed to evaluate the reliability and validity of the Arabic translated Resilience Scale among university students. A quantitative survey approach was employed to collect data from 353 undergraduate students in Saudi Arabia. Data were collected using a structured questionnaire consisting of the Resilience Scale (RS) and Beck Depression Inventory (BDI). Exploratory Factor Analysis and Confirmatory Factor Analysis were used to analyse the data. The results showed that the scale has excellent internal consistency. The results of exploratory factor analysis extracted five dimensions of resilience. Confirmatory factor analysis showed that the five-factor model has a good model fit. The resilience scores were negatively correlated with depression indicating good concurrent validity. The findings support the reliability and validity of the Arabic version of the Resilience Scale to be used in research with the Saudi population.